Basal Metabolism in Fish - Achmad Noerkhaerin Putra (JURNAL PERIKANAN DAN KELAUTAN, 2015)
Basal metabolism or minimal metabolism is the minimum amount of energy required to maintain vital functions in an organism. Basal metabolism represents the use of energy for things such as respiration, circulation of the blood, pulmonary ventilation, membrane transport of ions (especially of sodium and potassium), and muscle tone, repair and replacement of cells. To fully conclude on the effects of metabolism basal in fish diets, feeding managemnt, more research efforts are needed to provide the aquaculture industry, the scientific community, the regulatory bodies and the general public with the necessary information and tools.